Design and Outcomes of a Novel Keratoprosthesis: Addressing Unmet Needs in End-Stage Cicatricial Corneal Blindness. Issue 4 (April 2020) - Bakshi, Shaunak K.; Graney, John; Paschalis, Eleftherios I.; Agarwal, Shweta; Basu, Sayan; Iyer, Geetha; Liu, Christopher; Srinivasan, Bhaskar; Chodosh, James
Abstract : Purpose: The most commonly applied prosthetic devices for corneal blindness in the setting of severe cicatricial keratoconjunctivitis are the Boston keratoprosthesis type II and the modified osteo-odonto-keratoprosthesis, with these requiring either normal eyelid skin or a healthy cuspid tooth, respectively. For patients with neither attribute, we developed a new keratoprosthesis device combining positive aspects of both Boston keratoprosthesis type II and modified osteo-odonto-keratoprosthesis, which we have named the "Lux." Methods: Short-term postoperative outcomes for the Lux keratoprosthesis, best-corrected visual acuity (BCVA), device retention, and complications, were examined in a retrospective case series of 9 eyes of 9 patients implanted at 4 centers. Results: Seven of 9 (77.8%) eyes had cicatricial corneal blindness due to autoimmune disease and 2 (22.2%) from severe burns. Preoperative BCVA was ⩽hand motions in all patients. Three (33.3%) had previously received at least 1 keratoprosthesis in the affected eye, and 4 (44.4%) had previously undergone ≥1 therapeutic keratoplasty. One patient had 19 previous eye surgeries. The mean duration of postoperative follow-up was 18.7 months (range 7–28 months). BCVA of ≥20/200 was achieved in all 9 patients, with 2 (22.2%) reaching 20/20 at the last examination, and all 9 (100%) of the devices were retained. One recipient developed a retinal detachment 2 months after implantation. Two (22.2%) patients required placement of a glaucoma drainage device. Conclusions: The Lux keratoprosthesis was developed for patients with severe cicatricial keratoconjunctivitis who were otherwise not candidates for existing keratoprosthesis designs. Short-term outcomes after implantation of the Lux keratoprosthesis were encouraging.